A recurring nasal mass - Loo, Javier Lek Wei (2023)
A 56-year-old Chinese man presented to the Ear, Nose and Throat clinic with months of unilateral right-sided nasal obstruction. He reported occasional mucopurulent discharge and denied any hyposmia, episodes of epistaxis, or loss of weight and appetite. Nasoendoscopy revealed a right-sided nasal mass between the septum and middle turbinate. Magnetic resonance imaging (MRI) showed a 6.9cm right nasal cavity mass extending from the cribriform plate to the hard palate inferiorly, laterally abutting the ostiomeatal unit and medially abutting the nasal septum. No intracranial or orbital wall extension was seen (Fig. 1).